The Amulet of Samarkand : a Bartimaeus graphic novel - Stroud, Jonathan (Disney/Hyperion Books, 2010)
A graphic novel adaptation of the book in which Nathaniel, a young magician's apprentice, becomes caught in a web of magical espionage, murder, and rebellion, after he summons the djinni Bartimaeus and instructs him to steal the Amulet of Samarkand from the powerful magician Simon Loveland.